2021
DOI: 10.1186/s12870-021-02974-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic insights into the browning of the peel of bagging ‘Rui Xue’ apple fruit

Abstract: Background Bagging is one of the most important techniques for producting high-quality fruits. In the actual of cultivating, we found a new kind of browning in peel of apple fruit that occurs before harvest and worsen during storage period. There are many studies on metabonomic analysis of browning about storage fruits, but few studies on the mechanism of browning before harvest. Results In this study, five-year-old trees of ‘Rui Xue’ (CNA20151469.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
4
14
1
Order By: Relevance
“…Sunburn in fruits triggers the production of ROS, and their over-production leads to cell membrane peroxidation, extravasation of intracellular fluid, and an imbalance in metabolism. The over-production of O 2 − (the intermediate product of membrane lipid peroxidation) leads to oxidation in cells and causes degradation of lipids, which increases the MDA content in cells [3,[25][26][27]. In our study, the O 2 − content of BFN and BFA showed no significant differences, which indicates that at the beginning of sunburn injury, the higher scavenging effect in the pericarp cells overcomes the increasing concentrations of ROS [28].…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Sunburn in fruits triggers the production of ROS, and their over-production leads to cell membrane peroxidation, extravasation of intracellular fluid, and an imbalance in metabolism. The over-production of O 2 − (the intermediate product of membrane lipid peroxidation) leads to oxidation in cells and causes degradation of lipids, which increases the MDA content in cells [3,[25][26][27]. In our study, the O 2 − content of BFN and BFA showed no significant differences, which indicates that at the beginning of sunburn injury, the higher scavenging effect in the pericarp cells overcomes the increasing concentrations of ROS [28].…”
Section: Discussioncontrasting
confidence: 47%
“…The biochemical characteristics of different antioxidant enzymes make them have different inducibility in gene expression levels, which enables the antioxidant system to scavenge excessive ROS [6]. CAT, POD, PPO, SOD, and APX are the main antioxidant enzymes for scavenging reactive oxygen species (ROS) [3,33]. SOD is the first line of defense against oxidation in plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The supernatant (1 ml) was added into a mixture of titanium sulfate [100 μl, 5% (w/v)] and ammonia (200 μl), and the precipitate that formed was washed to remove pigments and then dissolved in sulfuric acid (5 ml, 2 M). The absorbance was measured at 415 nm, and a calibration curve (0–100 μM of H 2 O 2 ) was prepared to determine the concentration (Wang et al, 2021a ). For malondialdehyde (MDA) concentration, seedlings (0.12 g) were ground into homogenate with trichloroacetic acid [TCA, 1 ml, 10% (w/v)] and centrifuged at 4,000 g for 10 min.…”
Section: Methodsmentioning
confidence: 99%